2012
DOI: 10.1371/journal.ppat.1003065
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Subversion: A Novel Mechanism of Host Immune Evasion by Ebola Virus

Abstract: In addition to its surface glycoprotein (GP1,2), Ebola virus (EBOV) directs the production of large quantities of a truncated glycoprotein isoform (sGP) that is secreted into the extracellular space. The generation of secreted antigens has been studied in several viruses and suggested as a mechanism of host immune evasion through absorption of antibodies and interference with antibody-mediated clearance. However such a role has not been conclusively determined for the Ebola virus sGP. In this study, we immuniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
134
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(140 citation statements)
references
References 57 publications
3
134
1
2
Order By: Relevance
“…Virulence has been attributed not only to the membraneanchored GP but also to the soluble form of this protein, sGP, which results from RNA editing 18 . sGP increases endothelial permeability by acting as an activator of neutrophils and macrophages, which regulates the host immune response [19][20][21][22] .…”
mentioning
confidence: 99%
“…Virulence has been attributed not only to the membraneanchored GP but also to the soluble form of this protein, sGP, which results from RNA editing 18 . sGP increases endothelial permeability by acting as an activator of neutrophils and macrophages, which regulates the host immune response [19][20][21][22] .…”
mentioning
confidence: 99%
“…Notably, sGP protein is secreted by infected cells and is not present in virions. Previous study showed that to promote immune evasion, sGP serves as an antibody decoy or presents alternative non-neutralizing antibody epitopes for the humoral immune response [17,20,32]. Another study revealed that the 71 and 81 % of humoral immune response of symptomatic and asymptomatic individuals, respectively from Gabonese EBOV outbreaks mainly targets GP peptides [3].…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, Mohan et al gave mice a priming vaccination with a construct similar to ours, which only generated GP1,2, and subsequently boosted the mice with a construct that only produced sGP. 40 Using competition ELISA, they demonstrated that sGP could compete for GP1,2 antibodies very effectively, and that pseudovirion neutralization titers dropped after boosting with the sGP construct. They theorized that their findings might suggest that the sGP produced during an EBOV infection might subvert the antibody response to GP1,2 in individuals receiving a vaccine that produces only GP1,2 unless the virus is rapidly cleared.…”
Section: Discussionmentioning
confidence: 99%